The best of Adam Sharp [compact disc, unabridged] - Simsion, Graeme C. (Macmillan Audio, 2017)
From the #1 bestselling author of The Rosie Project and The Rosie Effect, an unforgettable new novel about lost love and second chances. On the cusp of turning fifty, Adam Sharp likes his life. He's happy with his partner, Claire, he's the music expert at trivia night at the pub, he looks after his mother and he does the occasional consulting job in IT--but there's something he can never quite shake off. And that's his nostalgia for what might have been, his blazing affair more than twenty years ago with Angelina Brown, a smart and sexy, strong-willed actress who taught him for the first time, as he played piano and she sang, what it meant to find--and then lose--love. How different might his life be if he hadn't let her walk away? And then, out of nowhere, from the other side of the world, Angelina gets in touch. What does she want? Adam has no idea, but this might be his only chance to re-capture the fire of his great lost love and live the life he was meant to. But does he dare to take the chance? The Best of Adam Sharp is about growing old and feeling young, about happy times and sad memories, about staying together and drifting apart, but most of all, it's about the power of the songs we sing when we fall in love.